Identifikasi Kesuburan Lahan Dan Pendapatan Petani Pasca Bencana Alam Gempa Bumi - Gufran, Gufran; Basir, Muhammad; Isrun, Isrun (Mitra Sains, 2023)
Central Sulawesi's 2018 earthquake, liquefaction, and tsunami caused liquefaction in Palu City's Balaroa and Petobo neighbourhoods. Land surface changes affected agricultural land area and soil fertility, which can affect farmers' income. Soil fertility indicates its nutrient-providing capacity. This study aims to assess agricultural land fertility, farmer income, and the best ways to recover from natural disasters. This descriptive study included all Petobo farmers affected by the earthquake and liquefaction. Purposive sampling tested 25 respondents. The field survey collected soil samples at coordinate points. Twelve soil samples were taken from six points at 20 cm and 40 cm depths. The samples were analysed at Tadulako University's Environmental and Natural Resources Analysis Laboratory. The results showed that Petobo Village's liquefaction-affected and unaffected areas had low fertility due to low C-organic and Potassium content, which prevented plants from using soil nutrients. Low soil fertility reduces crop production. Farmers earn an average of Rp. 1,422,857 per hectare, up to Rp. 4,633,929 per season per hectare. To increase soil fertility, farmers can use compost, manure, crop residues like legume plant stover, rice straw, and chemical fertilisers according to dosage.